Students’ practice on autonomous language learning behaviors: A narrative inquiry (ELT Forum: Journal of English Language Teaching, 2022)
The ability of learners to take an active role in their learning has attracted attention in foreign language learning as the focus of language teaching practice and theory have shifted to a student-centered approach. Thus, this study aimed at exploring how students employed autonomous language learning behaviors, such as planning, monitoring, and evaluating their learning, including the challenges that the students may find. By applying a narrative inquiry, this study focused on examining students’ experience in doing autonomous language learning behaviors and their challenges. The data were obtained using a semi-structured interview with four bilingual students who live at private Islamic boarding school. The findings revealed that they implemented autonomous language learning behaviors, yet they met some difficulties in doing those behaviors, such as the dilemma in determining the goals or the priorities to learn, the lack of motivation in doing those behaviors, the need of others to help them doing the behaviors and misunderstanding of the autonomous behavior concepts. The findings imply that the participation of the teacher's assistance and encouragement in implementing autonomous behaviors is crucial. Due to the limited data obtained in this study, future research can be done to explore more about autonomous behaviors. Keywords: autonomous; behaviors; challenges; learner autonomy